2016
DOI: 10.1016/j.jegh.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Protecting health workers from nosocomial Hepatitis B infections: A review of strategies and challenges for implementation of Hepatitis B vaccination among health workers in Sub-Saharan Africa

Abstract: The Sub-Saharan region has the highest Hepatitis B virus (HBV) rates, and health workers are at an increased risk of contracting nosocomial HBV infection. Vaccination of health workers plays a critical role in protecting them from sequelae of HBV; however, health-worker vaccination remains a challenge for many countries. This study was conducted to review practices/measures and challenges in the Sub-Saharan region relating to vaccination of health workers against HBV. We performed a literature review of articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 43 publications
(47 reference statements)
2
44
0
Order By: Relevance
“…Another area that was well studied was vaccines, where we observed knowledge gaps for different types of vaccines for hepatitis B (HBV), influenza and human papilloma viruses (HPV). Awareness of available HBV vaccines in our study (56–97%) was in line with a previous report . Cervical cancer caused by human papillomavirus (HPV) is the leading cause of cancer mortality among women in Africa .…”
Section: Discussionsupporting
confidence: 92%
“…Another area that was well studied was vaccines, where we observed knowledge gaps for different types of vaccines for hepatitis B (HBV), influenza and human papilloma viruses (HPV). Awareness of available HBV vaccines in our study (56–97%) was in line with a previous report . Cervical cancer caused by human papillomavirus (HPV) is the leading cause of cancer mortality among women in Africa .…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the priority in these countries should be the screening of HCWs for hepatitis B surface antigen and hepatitis B core antibody. [11] Such screening would help identify HCWs requiring vaccination and those with chronic infection who may benefit from antiviral treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, policies regarding adult vaccination including those involving HCWs are yet to be implemented in many African countries. [11,12] Several studies have investigated the level of hepatitis B vaccination coverage among HCWs in Africa and have reported full coverage as low as in 0.8% in Rwanda [13] and as high as 72.0% in Libya [14] . However, no study to date has pooled the available data on the current hepatitis B vaccination coverage among HCWs in the continent.…”
Section: Introductionmentioning
confidence: 99%
“…In term of applying protection, most respondents agreed for the usage of protections such as gloves or gowns while handling blood and blood products. Many studies demonstrated that personal protective equipment (PPE) are important and remain as the main preventive measure for HBV infection 14,21,22 .…”
Section: Discussionmentioning
confidence: 99%